Characterization of binary Ce–Ir alloy photocathodes. (18th June 2019) - Satoh, Daisuke; Shibuya, Tatsunori; Ogawa, Hiroshi; Tanaka, Masahito; Ikeura-Sekiguchi, Hiromi; Kuroda, Ryunosuke; Yoshida, Mitsuhiro; Sugawara, Hitoshi; Toyokawa, Hiroyuki
Abstract: Binary Ce–Ir alloys nominally containing 83, 78, 75, and 67 at% Ir were grown via arc melting in order to clarify the optimum composition for a Ce–Ir system to be used as photocathode material. Scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and X-ray diffraction (XRD) analysis were employed to characterize the microstructure and phase composition of these alloys. The results of the XRD analyses and SEM/EDX measurements indicated that single-phase homogeneous crystals composed of CeIr2 grains were successfully grown in the sample with an iridium content amounting to 67 at%. Through quantum efficiency (QE) measurements, it was revealed that the QE of the Ce-67 at% Ir alloy (CeIr2 phase) is a few times higher than that of the other Ce–Ir alloys.